Morphology, phylogeny, and ecology of the aphelids (Aphelidea, Opisthokonta) and proposal for the new superphylum Opisthosporidia - Karpov, Sergey; Mamkaeva, Maria A.; Aleoshin, Vladimir; Nassonova, Elena; Lilje, Osu; Gleason, Frank H. (Frontiers in Microbiology, 2014)
The aphelids are a small group of intracellular parasitoids of common species of eukaryotic phytoplankton with three known genera Aphelidium, Amoeboaphelidium, and Pseudaphelidium, and ten valid species, which form along with related environmental sequences a very diverged group. The phyla Microsporidia and Cryptomycota, and the class Aphelidea have recently been considered to be а deep branch of Holomycota lineage forming the so called the ARM-clade which is sister to the fungi. In this review we reorganize the taxonomy of ARM-clade, and establish a new superphylum Opisthosporidia with three phyla: Aphelida phyl. nov., Cryptomycota and Microsporidia. We discuss here all aspects of aphelid investigations: history of our knowledge, life cycle peculiarities, the morphology (including the ultrastructure), molecular phylogeny, ecology, and provide a taxonomic revision of the phylum supplied with a list of species. We compare the aphelids with their nearest relatives, the species of Rozella, and improve the diagnosis of the phylum Cryptomycota.